Analyzing the Role of Sustainability Reporting in Enhancing Corporate Image and Shareholder Value - Priyanto, Hengky Budi; Esso, Andi Sawe Ri (Riwayat: Educational Journal of History and Humanities, 2025)
The growing emphasis on environmental, social, and governance (ESG) issues has positioned sustainability reporting as a central mechanism for strengthening stakeholder trust and organizational legitimacy. Unlike traditional disclosures focused solely on compliance, sustainability reporting reflects a broader strategic orientation where transparency and accountability can reinforce both corporate image and shareholder value. This study explores the role of sustainability reporting by synthesizing insights from prior scholarly works, corporate case studies, and international frameworks. Adopting a qualitative literature-based approach, the analysis applies thematic coding to classify findings into areas such as corporate reputation, stakeholder engagement, risk management, and long-term financial performance. Data were collected from peer-reviewed journal articles, annual reports, and sustainability disclosures, with selection guided by inclusion criteria that prioritized relevance, credibility, and recency. Findings indicate that robust and credible sustainability reports serve as more than communication tools; they operate as governance instruments that reduce information asymmetry, strengthen legitimacy, and enhance investor confidence. Companies that integrate sustainability disclosures into their strategic positioningsuch as Unilever and Nestldemonstrate stronger reputational capital, enjoy lower capital costs, and attract long-term institutional investors. Conversely, symbolic or superficial reporting may undermine trust and trigger reputational risks. This study contributes theoretically by deepening the understanding of sustainability reporting as a driver of intangible assets such as image and reputation, while also offering practical guidance for firms aiming to balance transparency with value creation.